Content of matrix metalloproteinases in the intraocular fluid of patients with primary open-angle glaucoma - V. V. Chernykh; V. I. Konenkov; O. V. Ermakova; N. B. Orlov; А. N. Trunov (Сибирский научный медицинский журнал, 2020)
Aim of the study was to investigate the content of matrix metalloproteinases 2, 3, 9, in the intraocular fluid of patients with a developed stage of primary open-angle glaucoma. Material and methods. The study included 47 patients with advanced stage of primary open-angle glaucoma. The diagnosis is based on ophthalmological examination, including visual acuity, binocular ophthalmoscopy, spheroperimetry, echoophthalmography, optical coherence tomography, intraocular pressure measurement. Exclusion criteria were acute and exacerbation of chronic inflammatory diseases of the organ of vision, diabetic retinopathy, neovascular glaucoma, uveitis, hemophthalmia, autoimmune and tumor processes of any localization, as well as acute and exacerbations of chronic inflammatory diseases of any organs and systems. Patients who took for normalization of intraocular pressure drugs containing analogues of prostaglandins, that could activate the inflammatory process, were excluded from the study. 26 patients with a diagnosis of uncomplicated cataract made up a comparison group. All patients underwent determination of matrix metalloproteinases (MMP) 2, 3, 9 in the intraocular fluid. Results. Concentration of MMP-2 but not MMP-3 or MMP-9 is statistically significantly higher in the intraocular fluid of patients with a developed stage of primary open-angle glaucoma compared to individuals with uncomplicated cataracts. This may indicate importance of MMP-2 in the development of a local aseptic inflammatory process, impaired extracellular matrix and «remodeling» of the tissue structures of the organ of vision, leading to disruption of the outflow of intraocular fluid, which is an important factor in the pathogenesis of primary open-angle glaucoma.